2020
DOI: 10.1136/gutjnl-2020-323300
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome HBV DNA integration is independent of the intrahepatic HBV reservoir in HBeAg-negative chronic hepatitis B

Abstract: ObjectiveThe involvement of HBV DNA integration in promoting hepatocarcinogenesis and the extent to which the intrahepatic HBV reservoir modulates liver disease progression remains poorly understood. We examined the intrahepatic HBV reservoir, the occurrence of HBV DNA integration and its impact on the hepatocyte transcriptome in hepatitis B ‘e’ antigen (HBeAg)-negative chronic hepatitis B (CHB).DesignLiver tissue from 84 HBeAg-negative patients with CHB with low (n=12), moderate (n=25) and high (n=47) serum H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 46 publications
2
35
0
Order By: Relevance
“…Accordingly, Hsu et al 8 also demonstrated that the number of expressed viral integrations strongly correlated with levels of serum biomarkers associated with active viral replication and transcription (such as circulating levels of HBV DNA, HBV RNA, hepatitis B surface antigen, and hepatitis B corerelated antigen) in all of the samples at baseline. The findings of this investigation complement those of earlier studies 11,12 and further demonstrate that active HBV replication and HBV integration are linked processes.…”
supporting
confidence: 87%
“…Accordingly, Hsu et al 8 also demonstrated that the number of expressed viral integrations strongly correlated with levels of serum biomarkers associated with active viral replication and transcription (such as circulating levels of HBV DNA, HBV RNA, hepatitis B surface antigen, and hepatitis B corerelated antigen) in all of the samples at baseline. The findings of this investigation complement those of earlier studies 11,12 and further demonstrate that active HBV replication and HBV integration are linked processes.…”
supporting
confidence: 87%
“…In line with this, we have also shown evidence of HBV-DNA integration and clonal hepatocyte expansion in these patients considered immune-tolerant, indicating that hepatocarcinogenesis could be underway even in the early stages of HBV [ 157 ]. Moreover, in those subjects deemed as having immune control, evidence of HBV-DNA integration is again present, with the upregulation of genes involved in carcinogenesis [ 158 ]. The link between immunity and HBV DNA integration, however, remains tenuous, but with the use of novel technologies (e.g., tissue CyTOF and spatial transcriptomics) we can come to understand more about this relationship in the future.…”
Section: Viral Hepatitis Immune Imbalance and Hcc Developmentmentioning
confidence: 99%
“…As highlighted previously, the HBeAg-negative phase of chronic HBV infection may be associated with different virologic/clinical outcomes including HBeAg-negative chronic infection (serum HBV DNA < 2 × 10 3 IU/mL and normal ALT) and HBeAg-negative chronic hepatitis (moderate/high serum HBV DNA levels and elevated ALT) characterized by a higher risk of disease progression, the development of cirrhosis, and HCC [15]. A very recent study, analyzing, by whole-exome sequencing, HBV integration in liver tissue from 84 HBeAg-negative patients with low, moderate, and high serum HBV DNA, has shown that HBV integration occurs across all HBeAg-negative patients with CHB, including little-viremic patients with limited hepatic HBV reservoirs, and that by AUROC (Area Under the Receiver Operating Characteristics), HBsAg > 5 × 10 3 IU/mL identified the occurrence of HBV integration in the whole exome with the best diagnostic accuracy (86.5%) [65]. The preservation of HBsAg production independently of HBV replication leads us to hypothesize its role in viral persistence.…”
Section: Hbv Integration In Chronic B Infectionsmentioning
confidence: 99%